The effect of electrically conductive carbon black on properties of the linear low-density polyethylene - O. V. Kropotin; E. A. Rogachev; E. A. Drozdova; A. A. Kalenchuk; E. G. Glukhoverya; O. V. Maliy (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The effect of electrically conductive carbon black on the electrophysical and mechanical properties of the linear low-density polyethylene has been experimentally investigated. The structural parameters of carbon black have been determined, which have a significant effect on the electrical conductivity of carbon black and the electrical conductivity of polymer composite materials when it is used as a filler. It is established that the introduction of 10–20 wt. % carbon black in linear low-density polyethylene provides high conductivity of composite materials, while increasing their modulus of elasticity, but at the same time reduces elongation at break. It is shown that, in general, the studied carbon black is a promising filler in the development of electrically conductive polymer composite materials for electrical and radio engineering purposes.